IMPACT OF AUTOCRATIC LEADERSHIP STYLE ON JOB PERFORMANCE OF SUBORDINATES IN ACADEMIC LIBRARIES IN PORT HARCOURT, RIVERS STATE, NIGERIA - Dolly C, Kalu; Nonyelum P., Okpokwasili (International Journal of Research -GRANTHAALAYAH, 2018)
The study focused on the impact of autocratic leadership style on job performance of subordinates in academic libraries in Port Harcourt, Rivers State, Nigeria. The research design was a survey. The respondents were the 74 professional and para-professional staff working in the libraries studied. Data collection was through questionnaire. instrument titled “Autocratic Leadership Style on Job Performance of Subordinates in Academic Libraries (ALSJPSAL)” consisting of five (5) item statements. Analysis was done using frequency and mean for the research question. Findings of the study revealed that autocratic leadership style tends to develop dependent and uncreative subordinates who are afraid to take up responsibility. Autocratic leadership style, however, shows a significant negative impact on employee performance. This style of leadership tended to have work groups that were less productive and subordinates showed a high degree of dissatisfaction on the job. Therefore, autocratic leaders tend to limit the performance of subordinates. It is recommended that autocratic leadership style may be very valuable in situations where decisions need to be made as quickly and decisively as possible. Since autocratic leadership style leads to job dissatisfaction of subordinates, library heads should be closely monitored by the parent institution to check their excesses.